Association of Dietary Acid Load with Nonalcoholic Fatty Liver Disease and Advanced Liver Fibrosis in US Adults: Evidence from NHANES 1999–2018 - Cheng J; Wang W (Dove Medical Press, 2023)
Jin Cheng,1,2 Wei Wang2 1Department of Medicine, Wuhan University of Science and Technology, Wuhan, 430000, People's Republic of China; 2Department of Gastroenterology, Xiangyang Central Hospital, Affiliated Hospital of Hubei University of Arts and Science, Xiangyang, Hubei, 441021, People's Republic of ChinaCorrespondence: Wei Wang, Department of Gastroenterology, Xiangyang Central Hospital, Affiliated Hospital of Hubei University of Arts and Science, No. 136, Jingzhou Street, Xiangyang, Hubei, 441021, People's Republic of China, Tel +8613972088242, Email 32857107@qq.comBackground: Evidence for an association between dietary acid load (DAL) and non-alcoholic fatty liver disease (NAFLD) is scarce and controversial. We aimed to address whether an association exists between DAL and NAFLD/advanced liver fibrosis (AHF) among US adults in a nationally representative study.Methods: This was a cross-sectional study. We included adult participants from the National Health and Nutrition Examination Survey 1999- 2018. Potential renal acid load (PRAL) and estimated net endogenous acid production (NEAP) was calculated from the literature and NAFLD/AHF was diagnosed by noninvasive markers. We comprehensively explored these relationships using multivariate adjusted regression models, restricted cubic spline, stratification analysis, and sensitivity analysis.Results: We enrolled a total of 18,855 participants. All DAL metrics were positively and nonlinearly associated with NAFLD (all p-values < 0.0001), whereas NEAPF and NEAPR may be associated with AHF. In the stratified analysis, we found that the correlation between DAL and NAFLD exists in all ages and genders, but the effect of DAL seems to be more obvious in middle-aged, elderly and women. Similarly, we found that the effect of DAL on AHF was more significant in 45- 60-year-olds and women. Sensitivity analyses revealed stability of all results.Conclusion: DAL including PRAL and NEAP were positively associated with NAFLD in a large nationally representative cross-sectional study. NEAPF and NEAPR may be associated with increased odds of AHF. Adjustment for diet-dependent DAL requires age- and sex-specific strategies. Future prospective studies are needed to validate our findings.Keywords: nonalcoholic fatty liver disease, NHANES, liver fibrosis, dietary acid load, nutrient